Maskulinisasi Ikan Guppy (Poecilia Reticulata) Melalui Penggunaan Air Kelapa (Cocos Nucifera) Dengan Konsentrasi Berbeda - Tomi Malik; Mochamad Syaifudin; Mohamad Amin (Jurnal Akuakultur Rawa Indonesia, 2019)
Masculinization is one method of sex reversal technique that can direct the sex of fish. The aim of this research is to know the effect of different concentration ofcoconut waterto percentage of male guppy fish through immersion method.This research was conducted in August - October 2018 at Fisheries Basic Laboratory, Program Study of Aquaculture, Sriwijaya University. This research used completely randomized design (CRD) with four treatments and three replications i.e without coconut water (P0), coconut water 20%(P1), coconut water 30% (P2) and coconut water 40% (P3). The observed parameters were the percentage of male guppy, survival rate and water quality (temperature, pH, ammonia and dissolved oxigen). The result showed the percentage of male guppy was 46.66 % (P0), 70.00 % (P1), 80.00 % (P2) and 83.33 % (P3). Water  quality during maintenance were temperature 20.1 – 28.9 0C, pH 6.5 – 7.2, DO 3 – 6.8 mg/L, and ammonia 0.01 – 0.09 mg/L.  Masculinization is one method of sex reversal technique that can direct the sex of fish. The aim of this research is to know the effect of different concentration ofcoconut waterto percentage of male guppy fish through immersion method.This research was conducted in August - October 2018 at Fisheries Basic Laboratory, Program Study of Aquaculture, Sriwijaya University. This research used completely randomized design (CRD) with four treatments and three replications i.e without coconut water (P0), coconut water 20%(P1), coconut water 30% (P2) and coconut water 40% (P3). The observed parameters were the percentage of male guppy, survival rate and water quality (temperature, pH, ammonia and dissolved oxigen). The result showed the percentage of male guppy was 46.66 % (P0), 70.00 % (P1), 80.00 % (P2) and 83.33 % (P3). Water  quality during maintenance were temperature 20.1 – 28.9 0C, pH 6.5 – 7.2, DO 3 – 6.8 mg/L, and ammonia 0.01 – 0.09 mg/L.